Acute spontaneous and experimental poisoning by Solanum pseudoquina in cattle - Elaine Melchioretto; Daiane Ogliari; Tainara R. Tineli; Franciéli A. Molossi; Aldo Gava (Pesquisa Veterinária Brasileira)
ABSTRACT: The epidemiology, toxic potential, and clinical and pathological presentation of acute spontaneous and experimental poisoning by Solanum pseudoquina are described. In the spontaneous form, the plant was ingested by cattle on two properties, one in the municipality of Canoinhas and the other in Painel, Santa Catarina. The outbreak in Canoinhas occurred after some trees were felled, five cattle ingested leaves of the plant and showed staring eyes and muscle tremors; four died, and one recovered. On the Painel property, the outbreak occurred after the pruning of two trees, and two adult cattle ingested the plant and died. The information was provided by the owners, and only one bovine was subjected to autopsy in each outbreak. No lesions were evident at autopsy, and no material was collected for histological evaluation. In the experimental form, green leaves of S. pseudoquina were collected in the municipalities of Canoinhas, Painel and Urubici, in Santa Catarina. The leaves were administered orally to four cattle. Two cattle received a single dose of 40g/kg, one received two doses of 35g/kg, and another received six doses of 20g/kg. One of the animals that received the 40g/kg dose died without showing any clinical signs. The other animals showed apathy, muscle tremors, ataxia, motor incoordination, and difficulty getting up. At necropsy, cardiac alterations were observed in the cattle that received repeated doses of 20g/kg, namely hydropericardium and ventricular dilation, and liver congestion was observed in all the cattle. Microscopic examination showed mononuclear infiltrates in the heart samples of the four cattle (stained with hematoxylin and eosin - HE), which were mild, perivascular and between fiber bundles. Cardiomyocytes had multifocal cytoplasmic hypereosinophilia and pyknotic nuclei. The livers of all four cattle showed moderate congestion between the sinusoids. The anti-troponin immunohistochemistry (IHC) technique was performed on three heart samples and showed cardiomyocytes with decreased troponin C expression in the areas that corresponded to cardiomyocyte hypereosinophilia of varying intensity. S. pseudoquina has been shown to be potentially toxic to cattle when doses of more than 20g/kg are ingested.